Effect of Moxibustion on Size Reduction and Control of Filiform Warts: A Single Case Report - S, Ishwariyaa; J, Jebalin Josco; R, Yoga Priya; S, Geethanjali (Indian Journal of Integrative Medicine, 2025)
Cutaneous warts are the benign epithelial proliferative lesions caused by human papilloma virus infection. Warts have different types, among these filiform warts occur commonly on facial regions. In general population, the incidence is around 10% and is found to be higher in children and young adults. Moxibustion is a form of Traditional Chinese treatment that involves applying heat created by burning herbal materials—either directly or indirectly—to the acupoint or affected area. A 24-year-old male patient has been suffering from a filiform wart with sub-growths on his face in the left infraorbital region, measuring 2mm, for the past 2 years. The patient underwent an indirect, non-scarring moxibustion treatment over the filiform wart for 3 minutes daily, over a period of 21 days, in the OPD of International Institute of Yoga and Naturopathic Medical Sciences. After the 21 days of treatment there was a complete disappearance of sub-growths and decrease in the size from 2mm to 0mm of the filiform wart on assessment through the dimensions calculated using a centimetre ruler and residual discoloration persisted. Also, overall size of the filiform wart was reduced completely along with no further growth for the following months. This is the first single case study showing the efficacy of indirect moxibustion for reducing the filiform wart size. This case study shows that Indirect non-scarring Moxibustion can be an alternate intervention for the size reduction and prevention of filiform wart growth. Future research should aim to optimize the treatment by refining the choice of insulating material and extending the duration of the study to more comprehensively evaluate the therapeutic efficacy of this intervention.